Protective effect of methanolic extracts of thymus vulgaris against cyclophosphamide- induced DNA damage in mouse bone marrow cells using the micronucleus test - Abbas Salmani; Ali Kosari; Aliyar Pirouzi; Marjan Omidi; Mehdi Mohsenzadeh (Shiraz University of Medical Sciences, 2015)
Introduction: Cyclophosphamide is a chemo-therapeutic agent in the treatment of the various cancers and autoimmune diseases. This composition has cytotoxic and clastogenic properties. The purpose of this study was to evaluate, protective effect of methanol extracts of thymus vulgaris against DNA damage induced by cyclophosphamide in mouse bone marrow cells by the micronucleus test.Materials and Methods: In this study, the concentrations of extracts 375, 750, 1500 mg/kg body weight (bw) were injected intraperitoneally (ip), into mice for seven consecutive days. One hour after the last injection, cyclophosphamide 50 mg/kg bw intraperitoneally (ip) have been injected into mice. 24h after cyclophosphamide injection, the animals were sacrificed and samples of bone marrow were prepared and stained using standard methods. For each sample, 1000 cells of polychromatic erythrocytes (PCE) and the same frequence of normochromatic erythrocyte (NCE) and cells containing micronucleus of these were counted.Results: Cyclophosphamide increased the frequency of micronuclei polychromatic erythrocytes (MnPCE) and decreased cell proliferation (PCE/PCE+NCE). All doses of extracts significantly reduced the micronucleus frequency ratio (P<0.05). The cells proliferation ratio (PCE/PCE+NCE) also increased. The best effect in reducing the micronucleus frequency was 1500 mg/kg bw dosage.Conclusion: Thymus extract is able to reduce the clastogenic and cytotoxic effects of cyclophosphamide, seems to extract due to its antioxidant properties, has a protective role.